University of Malaya's low carbon approach : Evaluation of Clean Development Mechanism (CDM) potential / Okere Kelechi Justin - Justin, Okere Kelechi (2013)
Current human energy use and waste management practices have been associated with massive greenhouse gases emission resulting in climate change. Degradation of the already indebted environment and potential threat to sustainability due to the impacts is on the rise and has led to a unique synergy by world leaders to find antidotes. The United Nations Framework Convention on Climate Change (UNFCCC) through Kyoto Protocol in 1997 practically began championing the remedial effort mainly through one of the flexible mechanisms, Clean Development Mechanism (CDM), by which industrialized nations invest in green developments in developing nations and invariably earn carbon credits for greenhouse gas (GHG) emission reduction with a parallel greening of the development nation. University of Malaya is among the five pilot centres for low carbon city frame work assessment in Malaysia; hence this study was conducted to ascertain the eligibility of the institution for Clean Development Mechanism (CDM) as its transits to a low carbon campus. The focal points for the evaluation was electricity use and waste management practices as they fall into two of the six sectors eligible for CDM in Malaysia; energy efficiency and waste management. The objectives have been effectively analyzed adopting a conservatively prudent analysis incorporating primary and secondary data, onsite assessments and evaluation, perusal and integration of associated literature. Finally CDM methodologies AMS 11.N/ version 01.0 and AMS 111.AO./Version 01 are applied. Evaluation shows a positive trend for both cases; in a case study of the University‘s main library which forms less than 5% of the total floor area of the institutions building capacity, a CER of 4,841.2 tonnes worth about RM137,974.20 over a ten year crediting vi period is feasible just for lighting retrofitting. The bill savings from implementing this project activity is worth RM620,224.00 in a decade. The payback period is less than 3 years while the net profit could be about RM477,989.70, an average of almost RM48,000.00 annually. The anaerobic digestion of biodegradable waste for heat and power production also showed that CER of 1,764 tonnes worth RM 50,274.00 yearly is feasible. The annual average electricity generation capacity and bill savings of 55.6MW and RM19,640.00 respectively is estimated while a mega saving of over RM400,000 yearly from diversion of waste from the landfill is of high probability. There are potential for University of Malaya going for CDM, if the CDM secretariats prescribed procedures are followed, so as to achieve reduction in GHG emission. What could be done in University of Malaya should be replicated in other similar establishments with similar cases. This investigation is a pilot study of the potential economic and environmental gains accruable with University of Malaya or other similar institutions of same peculiar case participating in CDM. The result from this study has given a green light and encouraged a more detailed analysis on the energy use, waste management and associated technologies and policies for a successful transition to a more sustainable and low carbon campus status. Keywords: CDM, electricity use, waste management, carbon credit, Kyoto Protocol, greenhouse gas emission.